Redesign of the temporary storage facilities for hazardous and toxic waste at PT X - Kevin Daffa Prasetya; Kharisma Balqist Nabilah; Achmad Chusnun Ni’am (Faculty of Civil Engeneering and Planning - ITATS, 2023)
PT X is an industry engaged in the production of snacks. The processes and activities in the industry produce by-products, namely hazardous and toxic waste. All waste is stored in temporary storage, but based on observations, the extant temporary storage does not meet the government's requirements. Accordingly, PT X redesigned a temporary storage area following government requirements. This study aims to identify a temporary storage location that complies with government regulations for PT X. Recording the types, characteristics, and quantities produced by PT X, followed by existing observation, is followed by the calculation of facility needs according to SNI and individual calculations. This research analysis provides property and layout recommendations to enhance the condition of PT X's temporary storage for hazardous and toxic refuse.